ANALISIS PENGARUH ROE, DER, PBV, EPS DAN RISIKO SISTEMATIK TERHADAP RETURN SAHAM (Studi pada Perusahaan Property dan Real Estate yang Listed di Bursa Efek Indonesia Periode 2003 s.d 2007) - Ratnawati, Raden Roro Sari (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2009)
Stock return of properties and real estate in Indonesia have value tor investors. A lot of people invest their finance capital on properties can get increased their finance capital. Guard against loss performed in order to test the influence of ROE, DER, PBV, EPS and Systematic Risk toward stock return of properties and Real Estate. Companies that listed in Bursa Efek Indonesia (BE/) for period 2003-2007.Population of this research 35 company that listed in BEI 2003-2007 and getting beyond purposive sampling with criteria as (1) go public in 2003-2007 and (2) always seen annual financial report over period 2003-2007. Data that needed in this research taken from Indonesian Capital Market Directory (ICMD) 2003-2007 was acquired 23 sample company. Data analysis with multiple regression. Hypotheses test use t-statistic and F-statistic; at level of significance 5%. A classic assumption examination which consist of data normality test, multicolinierty test, heteroscedasticity test and autocorrelation test is also being done to test the data.Base on the result of this research, classic assumption has not founded, this indicate that the available data fulfill the condition to use multiple regression model. Empiric31 evidence of analysis show as Debt Earning Ratio (DER) and Systematic Risk have significant effect toward stock return at level of significances less than 5% (as 0,5%, 0,014% and 0,026% respectively). While five independent variable Return on Equity (ROE), Price to Book Value (PBV), and Earning per Share (EPS) nat have influence toward stock return at level of significances less than 5% (as 0,000%). Result of this research indicate that Return on Equity (ROE), Debt to Earning Ratio (DER), Price to Book Value (PBV), Earning per Share (EPS), and Systematic Risk use by investor to predict stock return of property company that listed in BEI at period 2003-2007.